Peranan sikap dalam gelagat kepatuhan zakat pendapatan gaji - Md. Idris, Kamil; Ayob, Ahmad Mahdzan (Universiti Utara Malaysia, 2002)
Reports show that compliance level of zakah among qualified Muslim employees is relatively low. One of the factors that has contributed to this phenomenon is the attitude of individuals. Literature has indicated that individual attitude towards regulated social activities influences his compliance behaviour in such activities. However, attitude towards regulated social activities is considered complex in nature. Due to this complexity, many researchers have suggested that attitude should be studied by dividing an object or issue into smaller and less complex elements on the basis of component parts, specific functions, or particular contexts. Thus, this study attempts to discover some components of attitude towards zakah on employment income and their implications to the compliance behaviour. Synthesis of literature suggests that studies on attitude and understanding its impact on behaviour may help one to formulate management strategies to increase the compliance level. This paper presents several components of attitude towards zakah on employment income and their impact on the compliance behaviour. The components of attitude were determined by using Factor Analysis on the 24 attitude items. Each factor was then named and treated as a new variable, which was then tested to see if any relationship exists with the compliance behaviour. The findings of this study indicate that attitude towards zakah on employment income can be divided into five categories, namely, General Attitude, Positive Attitude, Uncertain Attitude, Conditional Attitude, and Technical Attitude. These five categories of attitude were tested by using logistic regression analysis to see their relationship with the compliance behaviour, which is simply the dichotomously measured variable, of zakah payment on income. The test results show that the second, third, and fourth categories of attitude were positively and significantly related to the compliance behaviour.